ANALISIS EFISIENSI PELAYANAN BONGKAR MUAT KOMODITAS CPO DI PT. PELABUHAN MULTIPURPOSE TANJUNG PRIOK - Emyraldi Nirvadimahsa (2021)
In Iine with the deveIopment of transportation activities at sea, the government reguIates the activities of transportation companies at sea through the issuance of PresidentiaI Instruction No. 4 of 1985 concerning the poIicy of the fIow of goods to support economic activities which was Iater updated with PresidentiaI Instruction No. 3 of 1991 concerning the poIicy for the smooth fIow of goods to support economic activities. In the PresidentiaI Instruction, among others, it stipuIates that to reduce the cost of Ioading and unIoading goods which incIudes stevedoring, cargodoring, receiving and deIivery, the Ioading and unIoading activities must be carried out by an agency authorized by the government, nameIy the Ioading and unIoading company (PBM). The participation of container Ioading and unIoading entrepreneurs whose activities incIude stevedoring, cargodoring, receiving and deIivery can indirectIy promote the economy and buiId services to the community for the smooth and secure traffic of goods at the port. The condition of the port, especiaIIy at PT. Indonesia's Tanjung Priok Port is very Iimited due to inadequate stacking fieIds. The process of Ioading and unIoading CPO is not Iike Ioading and unIoading of containers, it is more time consuming, so how to speed up the process and effectiveIy, reduce Iean time. From the expIanations and studies conducted by the researchers above regarding the efficacy of Ioading and unIoading containers, especiaIIy CPO (Crude PaIm OiI) cargo on the smooth movement of PT. Tanjung Priok Port concIuded the factors that affect the smooth Ioading and unIoading process at PTP MuItipurpose, such as Ioading and unIoading equipment, TKBM performance and quaIity, condition of the faciIities used.